Orthogonal polarization spectral imaging: A new method for study of the microcirculation - Groner, Warren; Winkelman, James W.; Harris, Anthony G.; Ince, Can; Bouma, Gerrit J.; Messmer, Konrad; Nadeau, Richard G. (Nature medicine, 1999)
Different disease states, including diabetes, hypertension and coronary heart disease, produce distinctive microvascular pathologies. So far, imaging of the human microcirculation has been limited to vascular beds in which the vessels are visible and close to the surface (for example, nailfold, conjunctiva). We report here on orthogonal polarization spectral (OPS) imaging, a new method for imaging the microcirculation using reflected light that allows imaging of the microcirculation noninvasively through mucus membranes and on the surface of solid organs. In OPS imaging, the tissue is illuminated with linearly polarized light and imaged through a polarizer oriented orthogonal to the plane of the illuminating light. Only depolarized photons scattered in the tissue contribute to the image. The optical response of OPS imaging is linear and can be used for reflection spectrophotometry over the wide range of optical density typically achieved by transmission spectrophotometry. A comparison of fluorescence intravital microscopy with OPS imaging in the hamster demonstrated equivalence in measured physiological parameters under control conditions and after ischemic injury. OPS imaging produced high-contrast microvascular images in people from sublingual sites and the brain surface that appear as in transillumination. The technology can be implemented in a small optical probe, providing a convenient method for intravital microscopy on otherwise inaccessible sites and organs in the awake subject or during surgery for research and for clinical diagnostic applications.